Understanding the Impacts of Lockdown during COVID-19 Pandemic on Financial Threat and Psychological Response among Sarawak Adults - Nurkhalida, Suut; Aainaa Nasha, Mohamad Azlan; Siti Jamilah, Jamaluddin Jugah; Ting, Chuong Hock; Nurul Husna, Syaffa Amin; Muhmmad Ainul Rashyid Aris, Mohd Aris Fadillah; Zurraini, Arabi (USIM PRESS, 2021)
The Malaysian government announced the lockdown measures following the Coronavirus Disease 2019 (COVID-19) outbreak in mid-March 2020. This action unavoidably led to economic instability and negative psychological effects. The present study examines perceived financial threats and psychological impacts on Sarawak adults during lockdown for the COVID-19 pandemic. Data from 336 respondents were collected from all divisions in Sarawak using an online self-reported questionnaire that included sociodemographic, the Financial Threat Scale (FTS), and the Depression, Anxiety, Stress Scales 21 (DASS-21). Results showed that perceived financial threat was associated with the employment sector, the number of children, and the change in income during the lockdown period. Almost half (47.9%) of the respondents perceived moderate-to-severe financial threat, particularly self-employed persons and those who had reduced income during the lockdown. Negative psychological effects were found to be associated with the employment sector, marital status, number of children, and number of liabilities. In general, people who perceived severe financial threats were significantly associated with severe levels of depression, anxiety, and stress. The study provided some insights into the urgent need to build on strategic plans to mitigate the economic and psychological crisis for the affected communities.